Monte Carlo analysis of transient electron transport in wurtzite Zn1−xMgxO combined with first principles calculations - Ping Wang; Linlin Hu; Yintang Yang; Xuefei Shan; Jiuxu Song; Lixin Guo; Zhiyong Zhang (AIP Advances, 2015)
Transient characteristics of wurtzite Zn1−xMgxO are investigated using a three-valley Ensemble Monte Carlo model verified by the agreement between the simulated low-field mobility and the experiment result reported. The electronic structures are obtained by first principles calculations with density functional theory. The results show that the peak electron drift velocities of Zn1−xMgxO (x = 11.1%, 16.7%, 19.4%, 25%) at 3000 kV/cm are 3.735 × 107, 2.133 × 107, 1.889 × 107, 1.295 × 107 cm/s, respectively. With the increase of Mg concentration, a higher electric field is required for the onset of velocity overshoot. When the applied field exceeds 2000 kV/cm and 2500 kV/cm, a phenomena of velocity undershoot is observed in Zn0.889Mg0.111O and Zn0.833Mg0.167O respectively, while it is not observed for Zn0.806Mg0.194O and Zn0.75Mg0.25O even at 3000 kV/cm which is especially important for high frequency devices.